Regulatory T Cells in Elderly Patients With Asthma - Mota-Pinto, Anabela (2011)
Background: Airway walls in asthma present an accumulation of activated cells that determine bronchial structural changes and disease progression and severity. During the aging process, the immunoinflammatory response changes as a consequence of chronic antigenic stress. Objective: To evaluate T-cell subsets with regulatory functions associated with asthma in elderly patients. Methods: A group of 153 individuals (95 with controlled asthma and 58 healthy controls) aged over 65 years was studied. Blood samples were collected for fl ow cytometry analyses of CD3, CD4, CD8, CD56, CD56CD8, CD3CD4CD25, CD3CD4CD25CD127, CD4HLA-DR and TCRγδ. Results: Asthmatic patients showed a statistically significant increase in CD4+ T cells. CD3CD4CD25high and CD3CD4CD25highCD127high cells were also significantly increased in asthmatic patients, while CD3CD4CD25highCD127low cells had similar values in asthmatics and in the control group. CD4HLA-DR cells were within the normal range in both groups. A positive correlation between CD3CD4CD25highCD127low and CD4HLA-DR was observed and γδ T cells were signifi cantly decreased in the asthmatic patients compared to the controls. Conclusions: Since T cells with regulatory functions were within normal ranges or reduced in asthmatic patients compared to healthy controls, at least in basal conditions, it can be speculated that they probably play a limited role in chronic asthma in elderly patients. These data suggest an absence of a modulatory effect on the inflammatory response that characterizes asthma and allergy, which in turn would facilitate the persistence of disease in this population. Underlying inflammatory processes that are involved in chronic diseases associated with aging could provide an additional explanation for the attenuated differences observed between asthmatic and non asthmatic individuals.